Financial ratios with fuzzy logic approach. New estimation perspective - Luna Altamirano, Kleber Antonio; Sarmiento Espinoza, William Henry; Andrade Pesantez, Daniel Jacobo (Revista Venezolana de Gerencia, 2022)
The industrial sector of Cuenca represents an icon of development and progress of this city. The problem of studying this sector is that it calculates traditional financial ratios exposed to volatile contexts with high uncertainty. The aim of this research is to estimate financial ratios with fuzzy logic approach in industrial companies of Cuenca city, Ecuador, due to the great importance of estimating these ratios to determine the financial health of these organizations. The research is descriptive, with a quantitative approach, using the development of expert and counter-expertise techniques, applying a form of calculation through Triangular Fuzzy Numbers (TFNs), and confidence intervals, instruments of fuzzy logic. The results obtained at 80% and 90% of the degree of presumption, are equivalent to the bands [1,488, 1,506] and [1,494, 1,503] respectively, corresponding to the liquid ratio; in a similar way the other working capital ratios are presented in the study. This new estimate will allow directors and managers to make more accurate decisions for the benefit of their companies, overcoming traditional barriers to be framed in the objectivity and reality of the current market.